ANALYSIS ASSERTIVE SPEECH ACT IN "PURPLE HEARTS" MOVIE BY TESS WAKEFIELD - Hizkia, Nova; Handayani, Nurma Dhona (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2023)
Speech acts are what humans perform by speaking, according to linguistics. Speech acts can be seen in the movie as well as in daily life. This research focuses on the speech and the objectives of this research are to define the various speech actions especially assertive acts, and examine the most common ones used by the central character. Additionally, the texts in the form of movie scripts serve as the study's objects. The theory that is used in this research is Searle (1979) of speech acts. In this research, qualitative method was used to analyze the data. To determine which types in assertive act are most frequently used, and there were 15 utterances need to be examined in total. The findings of this research indicate that types use State, suggest, complain, claim, and report in assertive act. In conclusion, following the completion of the research, it contains suggestions to those who will utilize the similar research, especially pragmatics and the usage of the term assertive acts for communication in society or English community is needed.